Co-production and Uptake of Weather and Climate Services: Evidence of Welfare Impacts Among Farmers in Senegal Using A Dynamic Panel Data Approach - Chiputwa, Brian; Blundo Canto, Genowefa M.; Steward, Peter R.; Andrieu, Nadine; Ndiaye, Ousmane (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The present study aims to assess the impact of weather and climate information on the agricultural productivity and household income of smallholder farmers in Senegal. More specifically, authors assess the effectiveness of the Multidisciplinary Working Group (MWG) model that co-produces tailored weather and climate information in influencing management responses by farmers, ultimately leading to improved livelihoods in the form of higher crop yields and incomes.